Servant leadership in action how you can achieve great relationships and results - edited by Ken Blanchard (Oakland Berrett-Koehler Publishers, 2018)
We've seen the negative impact of self-serving leaders in every sector of our society. Not infrequently, they end up bringing down their entire organization. But there is another way. Servant leaders lead by serving their people, not by exalting themselves. In this collection, edited by legendary business author and lifelong servant leader Ken Blanchard and his longtime editor Renee Broadwell, leading businesspeople, bestselling authors, and spiritual leaders offer tools for implementing this proven--but for some, still radical--leadership model.
Includes index.
Keywords: Servant leadership